Channel incision by headcut migration: Reconnection of the Colorado River to its estuary and the Gulf of California during the floods of 1979–1988. Issue 22 (11th August 2020) - Nelson, Steven M.; Kendy, Eloise; Flessa, Karl W.; Rodríguez‐Burgueño, J. Eliana; Ramírez‐Hernández, Jorge; Rivas‐Salcedo, Tomás E.
Abstract: The macrotidal Colorado River Delta at the northern end of the Gulf of California in Mexico is hydrologically complex. We review historical accounts, data, field notes and photographs to evaluate the hydrological processes active on the delta prior to the advent of upstream dams. We also employ satellite imagery as well as recent LIDAR data to illustrate the critical role played by headcut erosion in restoring the river's fluvial/tidewater connection during the 1979–1988 floods. Prior to human manipulation, the river's contribution of fresh water to the Gulf was periodically interrupted by natural overflowing, avulsing, and flooding into the sub‐sea level Salton Sink on the north slope of the delta plain. River flow south towards the Gulf was also subject to occasional overflow into Laguna Salada, another sub‐sea level basin. In the mid‐20th century, the Delta was disconnected from its fluvial supply following installation of upstream dams and reservoirs. A tidal sediment obstruction developed in the estuary channel, forming a final barrier to fluvial connectivity. Release of Colorado River floodwaters into Mexico between 1979 and 1988 provided a natural experiment on the hydrological response of a long‐disconnected macrotidal delta to restoration of fluvial supply. Abstract : During the 1980s, floodwaters reached Mexico's Colorado River Delta for the first time in a quarter century providing a natural experiment on the hydrological response of a long‐disconnected macrotidal delta to restoration of fluvial supply. We analysed historical aerial photos, satellite images, and LiDAR data to build a chronology of hydrological developments as the river restored its tidewater connection to the Gulf by the process of headcut migration and channel incision.